Relationship between Depression Symptoms and Different Types of Measures of Obesity (BMI, SAD) in US Women - Yang Zhou; Guifang Yang; Wen Peng; Hongliang Zhang; Zhenyu Peng; Ning Ding; Tao Guo; Yuzhong Cai; Qijian Deng; Xiangping Chai (Behavioural Neurology)
Objective. To estimate the relationship between obesity (defined by both BMI and SAD) and various levels of depressive symptoms in women in the United States. Methods. This is a cross-sectional design. All data were collected from NHANES 2011-2012 and 2013-2014. The Patient Health Questionnaire (PHQ-9) was the primary variable used to index depressive symptoms. SAD was assessed using an abdominal caliper. We stratified participates into three groups according to SAD (trisection): T1: low (11.8-18.4 cm), T2: middle (18.5-22.8 cm), and T3: high (22.9-40.1 cm). Other data were collected following the NHANES protocols. We aimed to investigate the effects of obesity on the depression in the NHANES populations. Results. A total of 4477 women were enrolled in the final study population. Participants with a high SAD had the highest risk of clinical depression symptoms (OR=1.2, 95% CI: 1.1-1.4), which was, in particular, the case for moderate-severe depression (OR=1.4, 95% CI: 1.1-1.7) and severe depression (OR=1.4, 95% CI: 1.0-1.9). We also found a significant relationship between SAD and BMI (r=0.836). We did, however, not find a significant relationship between BMI and severe depression. Conclusions. SAD had a better correlation with clinical depression symptoms than BMI, especially regarding severe depression symptoms.